2018
DOI: 10.3389/fimmu.2018.02019
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Internalization of Anti-DNA Antibodies by Human Monocytes Induces Production of Pro-inflammatory Cytokines Independently of the Tripartite Motif-Containing 21 (TRIM21)-Mediated Pathway

Abstract: Anti-DNA autoantibodies are a hallmark of systemic lupus erythematosus (SLE). A subset of anti-DNA IgG autoantibodies is cell-internalizable; thus they can enter living cells in the form of free IgG. However, the contribution made by the Fc region of internalized free-form IgG to the cytokine response has not been studied, despite the recent discovery of tripartite motif-containing 21 (TRIM21), a cytosolic Fc receptor involved in immune signaling. This study used an internalizable IgG anti-DNA antibody (3D8) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…HEK293F cells were cultured in serum-free FreeStyle 293 media (ThermoFisher Scientific; cat# 12338018) with 8% CO 2 and shaking at 130 rpm in the 37 °C incubator. FreeStyle 293-F cells (100 ml) at a density of 2 × 10 6 cells/ml were transfected with 200 μg of KV10 plasmid encoding an Ab gene using 400 μg of polyethylenimine (PEI) reagent with a molecular weight of ~25 kDa (Polyscience; cat# 23966-2), a final PEI concentration of 4 μg/ml 46 . After 7 days, the culture supernatants were harvested by centrifugation, and two chimeric MC-IgY and two chimeric MH-IgG proteins were purified by affinity chromatography using Protein L (GE Healthcare; cat# 17-5478-01) and Protein A column (GE Healthcare; cat# 17-1279-01), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293F cells were cultured in serum-free FreeStyle 293 media (ThermoFisher Scientific; cat# 12338018) with 8% CO 2 and shaking at 130 rpm in the 37 °C incubator. FreeStyle 293-F cells (100 ml) at a density of 2 × 10 6 cells/ml were transfected with 200 μg of KV10 plasmid encoding an Ab gene using 400 μg of polyethylenimine (PEI) reagent with a molecular weight of ~25 kDa (Polyscience; cat# 23966-2), a final PEI concentration of 4 μg/ml 46 . After 7 days, the culture supernatants were harvested by centrifugation, and two chimeric MC-IgY and two chimeric MH-IgG proteins were purified by affinity chromatography using Protein L (GE Healthcare; cat# 17-5478-01) and Protein A column (GE Healthcare; cat# 17-1279-01), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Soon after, they reported similar findings with anti-DNA antibodies as well [13]. Initially, these findings met with skepticism, but gradually, many studies confirmed this phenomenon [14][15][16]. The mechanisms responsible for internalization are multifarious.…”
Section: Penetration Of Anti-dna Antibodies Into Live Cells (Figure 1)mentioning
confidence: 76%